Pengaruh Pembelajaran Ilmu Tajwid Terhadap Peningkatan Kemampuan Membaca Al-Qur’an pada Jama’ah Masjid An-Nur Purwosari Pringsewu - Selvia, Devi Sela Eka; Asrori, Achmad; Suri, Indah Resti Ayuni; Sintia, Yola (Universitas PGRI Semarang, 2024)
In daily life, a Muslim cannot escape from the guidance and teachings of the Qur'an because it is a guideline and Rahmatalil Alamin for all mankind in this world, which must be studied and practiced by a Muslim. To make the basic foundation of life and guidelines in human life, of course it must begin with the ability to read the letters of the Qur'an and be able to understand the laws of tajwid. This thesis discusses the learning of tajwid science to improve the ability to read the Qur'an in the congregation of the An-Nur Purwosari Pringsewu Mosque which aims to understand the learning of tajwid science so that it can improve the ability to read the Qur'an and to find out whether there is an influence in learning tajwid science to improve the ability to read the Qur'an in the congregation of the An-Nur Purwosari Pringsewu Mosque. This study uses a quantitative approach with a descriptive approach, with data collection techniques through tests (written and practical), and observation. The subjects of this study were the congregation of the An-Nur Purwosari Pringsewu Mosque, which was attended by the majority of mothers. Primary data was obtained directly from respondents through written tests and practical tests on learning the science of tajwid on improving the ability to read the Qur'an. All data from respondents' answers were used to describe the effect or not of learning the science of tajwid on improving reading the Qur'an at the An-Nur Mosque Congregation. The results of the study showed that the Congregation of the An-Nur Purwosari Pringsewu Mosque in carrying out the learning of the science of tajwid was very enthusiastic to understand the science of tajwid with only minimal abilities related to the science of tajwid. In this study, the learning material for the science of tajwid was delivered from the most basic, so that the mothers of the congregation could easily understand and experience many changes in their ability to read the Qur'an according to the science of tajwid, because they routinely studied it. Judging from the results of the hypothesis shows that the value of Sig = 0.000 which means that the value is smaller than the criterion value a = 0.05 (Sig 0.000 0.05), and also obtained the t-value from the t-test table of 17.542 with a significance level of 5% sample 30 then obtained r-table of 1.697 (t-count 17.542 r-table 1.697) so it can be concluded that H0 is rejected because there is a significant influence between learning tajwid science on improving the ability to read the Qur'an in the congregation of the An-Nur Purwosari Pringsewu mosque. From these results it is necessary to know what percentage of the influence is, seen from the results of the correlation / relationship value (R) which is 0.957. From the output, the coefficient of determination (R Square) is obtained as much as 0.917, which shows that the influence of the independent variable (Learning Tajwid Science) on the dependent variable (Improving the Ability to Read the Qur'an) is 91.7%. So 91.7% of learning Tajwid science has an effect on improving the ability to read the Qur'an in the congregation of the An-Nur Purwosari Pringsewu mosque.